Identifying the Needs of Faculty Members to Deliver Online Training after the Pandemic - Yasemin Demiraslan Çevik; Dilek Avcı; Şeyhmus Aydoğdu; Sibel Somyürek (Uluslararası Türk Eğitim Bilimleri Dergisi)
The main purpose of this study is to identify the needs of faculty members in delivering online education after the pandemic. The participants in the study consisted of 166 faculty members working in higher education institutions at a national level, selected through convenience sampling. A needs analysis questionnaire was developed by the researchers to collect data for the study. The questionnaire consisted of 4 sections: 'Demographic characteristics and professional experience, the experience of online education during the pandemic period, online teaching needs, and preferred forms of support'. According to the research results, the participants had difficulties mainly in ensuring student participation rather than planning lessons and managing technical processes while teaching during the pandemic process. However, it was found that participants largely preferred a face-to-face learning environment after the pandemic. In addition, participants indicated that their need for self-improvement in all sub-competencies related to online education was at a low level. It was also noteworthy that the types of support participants preferred to gain online learning skills were similar before and after the pandemic. The research findings were discussed in the context of the literature, and recommendations were made.